The dynamics of a controlled streamer discharge at moderate air pressures - Sosnin, Eduard A.; Panarin, Victor A.; Skakun, Victor S.; Baksht, Evgenii Kh; Kuznetsov, Vladimir S.; Sorokin, Dmitry A. (Russian physics journal)
Relying on the analysis of the streamer discharge research data, a classification of the streamer discharges into free and controlled events is proposed. Controlled (linear and branched) streamers are formed in air at the pressures from 30 to 150 Torr. Using the method of high-speed photography, the propagation velocities and the glow structure of the ionization waves are obtained at their start, during deceleration, and in the branching point. It is found out that the ionization wave glow consists of two parts - the principal wave and precursor glows. It is shown that the precursor glow is much less intensive that that of the principal wave and contains mainly the 2(+) N-2 and 1(-) N-2(+) bands. This finding and the fact that the experiment in this study has been conducted at moderate air pressures provide an explanation why this glow was not observed earlier. The data obtained can be useful for designing theoretical test models.